BECOMING “AMERICAN”: HOW ARE WE CULTURALLY AWARE? - Sugeng Purwanto (Universitas Stikubank (UNISBANK) Semarang, 2013)
The current study is aimed at investigating to what extent the seventhsemester students of FBIB- UNISBANK are aware of American culture uponcompletion of Cross-Cultural Understanding (CCU) class, assigning 25 students.The subjects were given a survey questionnaire, focusing on the four variables,(1) Fashion, (2) Food, (3) Dating, and (4) General Codes of Conducts.Interviews were also held to verify their responses and to further investigatethe stance toward the American culture. The findings show that most of thestudents have positive attitudes towards American Culture, and some of them haveadopted the America’s ways of life in terms of fashion, food, and dating. Only fewof them adopted American social conducts with little modification. However, theinterviews yields that they are culturally adoptive at the cognitive level inthe sense that they still maintain their oriental thought patterns. Individualismand honesty refer to different things as viewed by both countries. Finally, thestudy recommends that CCU class be made ‘competence-based’ with the studentsactively exploring information for themselves. Further researches are stillwidely open.Key Words: culture, American, fashion,foods, dating, codes of conducts